2010
DOI: 10.1007/s12565-010-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of an anatomical technique for visualizing the mode of climbing fiber innervation in Purkinje cells and its application to mutant mice lacking GluRδ2 and Cav2.1

Abstract: In the adult cerebellum, a single climbing fiber (CF) innervates proximal dendrites of Purkinje cells (PCs). This mono-innervation is established by developmental elimination of surplus CFs through homosynaptic competition among multiply-innervating CFs and heterosynaptic competition between CFs and parallel fibers, i.e., granule cell axons innervating distal PC dendrites.Although developmental process of CF mono-innervation and its defects in mutant and experimental animal models have been extensively studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Dextran Alexa 594 (DA-594; Invitrogen) was injected into the inferior olive to label CFs as described (46). After 4 d of survival, mice were fixed by transcardial perfusion and parasagittal cerebellar sections (50 μm in thickness) were cut (11,15,25).…”
Section: Methodsmentioning
confidence: 99%
“…Dextran Alexa 594 (DA-594; Invitrogen) was injected into the inferior olive to label CFs as described (46). After 4 d of survival, mice were fixed by transcardial perfusion and parasagittal cerebellar sections (50 μm in thickness) were cut (11,15,25).…”
Section: Methodsmentioning
confidence: 99%
“…Loss of planarity prior to cell death can also alter synaptic inputs through interdigitation of neighbouring dendritic trees. Multiple climbing fibre (CF) innervation can arise via CF transverse branches (Miyazaki & Watanabe, ) and disruption to the specificity of granule cell input can occur through ascending axons making synaptic contact with more than one Purkinje cell and/or parallel fibres making additional contacts with the same Purkinje cell (Napper & Harvey, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent morphological study also showed that ectopic CF branches in GluD2 KO mice innervate limited areas in the distal dendritic tree of PCs, and that transverse CF collaterals elongating in the outer molecular layer near the pial surface have glutamatergic terminals around dendrites of multiple neighboring PCs (Miyazaki and Watanabe, 2010). These elongated transverse CF collaterals and ectopic synapse formation occur mutually among neighboring PCs (Miyazaki and Watanabe, 2010). Thus, CFs of GluD2 KO mice are considered to activate their main target PCs through ascending main branches and also neighboring PCs through transverse collaterals.…”
Section: Discussionmentioning
confidence: 99%
“…GluD2 is essential for the formation and stabilization of PF–PC synapses by interacting with Cbln1 that binds to neurexin at PF terminals (Matsuda et al, 2010; Uemura et al, 2010). Thus, the GluD2 knockout (KO) mouse (Kashiwabuchi et al, 1995) has been shown to exhibit various defects in synaptic wiring and neuronal response: (1) the number of PF–PC synapse is reduced to nearly half of that of control mouse, which results in emergence of numerous free spines in PC distal dendrites (Kurihara et al, 1997; Ichikawa et al, 2002; Takeuchi et al, 2005), (2) CFs extend distally along PC dendrites, take over spines from PFs and form ectopic synapses on PC distal dendrites (Ichikawa et al, 2002), (3) transverse collaterals of CFs that run perpendicularly to the plane of PC dendritic tree are markedly elongated and form ectopic synapses on distal dendrites of neighboring PCs along the mediolateral axis (Miyazaki and Watanabe, 2010; Miyazaki et al, 2010), (4) stimulation of the aberrant CFs in cerebellar slices induces atypical excitatory postsynaptic responses with slow rise time and small amplitudes in PCs which are associated with calcium transients localized to distal dendritic arbors (Hashimoto et al, 2001; Miyazaki et al, 2010), and (5) PCs in GluD2 KO mice in vivo exhibit atypical “clustered firing (Cf)” (Yoshida et al, 2004), which is considered to be induced by ectopic CF inputs to PC distal dendrites. Thus, GluD2 KO mice provide an excellent model to study how altered CF to PC wiring affects population activity of PCs and functional microzonal organization in vivo .…”
Section: Introductionmentioning
confidence: 99%